THE EFFECT OF SMART BOX MEDIA ON ORAL HEALTH KNOWLEDGE AMONG ELEMENTARY SCHOOL CHILDREN AGED 9–11 YEARS AT SDN KELAYAN BARAT 3 BANJARMASIN - Dinda Ayu Febrianti; Alexander Sitepu; Diana Wibowo; Riky Hamdani; Norlaila Sarifah (FKG ULM, 2025)
Background: Oral health problems are still one of the things that cannot be overcome in Indonesia, especially in children. This is due to behavioral factors ignoring oral hygiene based on lack of knowledge. This knowledge can be improved by conducting health promotion using attractive and interactive media such as smart box media. The advantages of this media are easy to use and children can learn while playing which is then able to develop children's cognitive abilities optimally. Purpose: To analyze the effect of smart box media on oral health knowledge in students aged 9-11 years. Methods: Quasi-experimental research with non-equivalent control group design with purposive sampling technique. The population of this study were students aged 9-11 years at SDN Kelayan Barat 3 Banjarmasin with a sample of 48 respondents. The instrument used was a questionnaire with 12 questions. The analysis used was Wilcoxon and Mann whitney test. Results: The Wilcoxon test showed that a significant increase in knowledge occurred after the intervention using smart box media (p<0.001). Conclusion: Smart box media is effectively used in oral health promotion to improve children's oral health knowledge in students aged 9–11 years. Keywords: Smart box; dental health education; oral health knowledge.